Effects of genotype, seed P concentration and seed priming on seedling vigor of rice - Pame, A.R.; Kreye, C.; Johnson, D.; Heuer, S.; Becker, M. (Cambridge University Press, 2015)
Seedling vigor is important to help ensure good crop establishment. In direct-seeded rice, this is particularly relevant when soil conditions are marginal. In Asia, about one third of the area of rainfed rice is situated on unfavorable soils, many of which are low in plant available P. In such environments, as farmers tend to have few resources, options to overcome poor crop establishment should be low cost and preferably seed-based. The P content of seed depends on genotype and can be augmented by soaking seeds in a P-containing solution prior to seeding (P-priming). In addition, the presence of the Pup1 quantitative trait locus can reportedly confer tolerance to low soil P availability. We tested combinations of seed priming (unprimed control, water priming, P-priming), and inherent seed P concentrations in contrasting rice genotypes (DJ123, Sadri Tor Misri), and two near isogenic sister lines of IR74 with (+Pup1) and without (?Pup1) the Pup1 QTL. Treatment effects on germination were studied in Petri dishes, while seedling growth and P accumulation were assessed using pots with P deficient soil. Germination was less than 75% in seeds with low seed P content. Seed priming with both water and P enhanced germination and seedling growth. In plants growing from high P seeds, water priming outperformed P-priming. In Sadri Tor Misri with low seed P, we observed a tendency for better performance in some parameters when P-primed. While the presence of the Pup1 QTL in IR74 increased shoot biomass and total root length, these effects could be further enhanced by water priming. Combining genetic and seed management approaches may contribute to improved rice establishment in P deficient soils but its effectiveness depends on genotype and seed attributes.